Issues and Challenges in the Process of Assessment - Agaj, Teuta (European Journal of Social Science Education and Research, 2015)
Assessment is a broad concept which means it is part of the whole educational process of teaching and learning. The variety of methods that teachers use to evaluate and measure the student’s learning progress and skill acquisition are referred by the term assessment. Assessment shapes how teachers teach and how students learn. The assessment of student’s achievements is a pedagogical dialogue between teacher-student for the quality of teaching, learning and knowledge.Assessment especially continuous assessment is a very important tool that teachers should use in the classroom because by using it a wealth of information to guide classroom practice and to manage learning and learners can be provided. Assessment tells us the truth about an education system, then about the qualities of students and their work.It has an important role in education and it is necessary to help students learn, to help students become knowledgeable, to help students gain insight into their learning and understanding, to teach effectively etc.Since making assessment an integral part of daily instruction is a challenge, this paper examines the process of assessing student’s knowledge, types of assessment and the assessment of L2 writing. It also focuses on the issues and challenges in the process of assessment.
Keywords: assessment, reliability, validity, L2 assessment.